PENTRAXIN 3 AND ITS ROLE IN PERIODONTITIS - VARGHESE MATHEW; SANKARI. M; KRITIKA JANGID. (International Journal of Pharma and Bio Sciences, 2015)
Pentraxin 3 belongs to the family of Pentraxins. It is similar to acute phase proteins like C-reactive proteins (CRP) and Serum Amyloid Proteins (SAP). Pentraxin 3 molecules are produced by various cells like dendritic cells, macrophages, neutrophils, endothelial cells and myeloid cells, other than hepatic tissue in response to inflammation. Periodontitis is caused by gram negative bacteria associated with the biofilm attached to the teeth and the host response elicited by the endotoxins produced by the microorganisms. As a result of these inflammatory reactions there are elevated levels of various acute phase proteins in the plasma. Mediators produced by the host that contribute to tissue destruction include acute phase proteins, prostaglandins and cytokines. Pentraxins are such classical acute phase proteins belonging to a super family of evolutionarily conserved proteins considered as markers of inflammation. Therefore, the use of Pentraxin 3 as a marker to quantify the amount of inflammation and disease state has substantial relevance.